Health Status, Occupational Hygiene & Safety Practices among Female Workers in Bangladesh - AbulKashem Obidul HUQ; HabibunNabi Muhammad Ekramul MAHMUD; Kazi Mohammad Formuzul HAQUE (Tehran University of Medical Sciences, 2015)
Background: With the rising of baking industries in Bangladesh, more female workers are surprisingly engaged compared to male workers. The major aim of this study was to observe the working conditions, available safety facilities and hygiene maintained by the female workers. Methods: A cross sectional survey was carried out among the randomly selected 384 female workers from different baking industries located at Dhaka and Tangail regions in Bangladesh by a well-designed semi-structured questionnaire. Results: About 33% of all respondents opined the machine room was congested, 27% narrow packaging and sealing room while 37% unhealthy storage areas. Two industries did not have proper accident prevention facilities. Although all the industries had monitoring personnel hygiene practices, about 40% of the workers were found not strictly maintaining some basic personal hygiene criteria. Socio-demographic result showed that the workers education level and monthly family income were poor. About 59.1% of all workers were suffering from various degrees of Chronic Energy Deficiencies (CED). It was also observed that nutritional status of the workers significantly related to their expenditure of the foods and working loads (χ2 Value < 0.05). Conclusion: The survey revealed that the occupational hygiene and safety practices were not at satisfactory level in some selected food industries in Bangladesh. The currently available food safety tools and system like Hazard Analysis and Critical Control Points (HACCP) should be adapted by the industries and concurrently ensure the sufficient wages for workers.   Keywords: Industrial female workers, Occupational hygiene, Safety practices, Chronic Energy Deficiencies (CED)